93.7k views
1 vote
If m∠A = m∠B and m∠A + m∠C = ∠D, then m∠B + m∠C = ∠D Which property is shown?

User Mina Fawzy
by
5.1k points

1 Answer

5 votes

Answer:

Substitution Property

Explanation:

So we know that:


m\angle A=m\angle B

And we also know that:


m\angle A+m\angle C=\angle D

And by using a specific property, we get that:


m\angle B+m\angle C=\angle D

Essentially, we substituted B for A.

So, this is an example of the substitution property, where if two sides/angles are congruent, we can substitute them for each other.

User AntonK
by
5.7k points